Pictures of costumes worn by Mr. Wild - Geiger, And. (artist):::Creator::::::::::::; Scheller (engraver):::Contributor::::::::::::
Color lithograph of Franz Wild wearing costumes as Don Juan in the opera by Mozart; and as Server in the opera Norma by Bellini